Physical methods for materials characterisation - Flewitt, P. E. J. (Series in materials science and engineering)
"This completely revised and expanded new edition covers the full range of techniques now available for the investigation of materials structure and accurate quantitative determination of microstructural features within materials. It continues to provide the best introductory resource for understanding the interrelationship between microstructure and physical, mechanical, and chemical properties, as well as selection and application of techniques for both basic and applied studies. In particular, changes have been made to reflect developments in analysis of nanoscale and biological materials"--